Improving the academic self-efficacy among students using Akademi Youtuber application / Hamidah Mat ... [et al.] - Mat, Hamidah; Yusof, Muhammad Suffi; Mohd Noor, Nur Emyra; Ayob, Nur Rahayu; A. Saiman, Savina; Zulkfli, Zuly Rahmi (Universiti Teknologi MARA, Kedah, 2024)
To succeed in the twenty-first century, today's generations must be exceedingly competitive and knowledgeable in many areas. The Education 4.0 effort is focused on the diffusion of technology in education. Therefore, today’s students need to embrace digital learning rather than just being taught via memorization exercises and rote learning. The purpose of this research is to investigate the ways in which the Akademi Youtuber application (AYU application) assists students in developing their self-directed learning abilities and serves as a reference for both educators and parents. A group of twenty-five information technology specialists and content experts evaluated the content and usability of the AYU application. It was determined, on the basis of the percentage of agreement among the experts (91.2 percent agreement), that AYU application is appropriate for developing self-learning abilities and can be readily accessible by students, parents, and instructors.